Caring for authors and activists in the classroom: An activist-caring teaching approach - Apoifis, Nicholas (Critical Studies in Teaching and Learning, 2023)
Neoliberal capitalist intrusions into university classrooms are pervasive, incessant, and pernicious. How we perform and enact care in classrooms is shaped by this prevailing ideology. However, its ideological and material reach is not absolute. Using insights from radical pedagogies, militant ethnographic, and narrative approaches, I reimagine and reconfigure care in the classroom by implementing an activist-caring teaching approach. I discuss the ways in which I practice and perform a relationship of care to writers and activists whose work and struggles I teach in my classes, struggles of resistance, emancipation, and revolution. Specifically, I lay out my own classroom strategies that enact this relationship, interactions with people some of whom are dead and many of whom I have never met. I argue that this is important for the practice of solidarity and radical notions of care and offers a novel way to resist and refuse neoliberal intrusions into university teaching spaces.